Barriers and facilitators of cervical cancer screening literacy among rural women with HIV attending rural public health facilities in East Central Uganda: a qualitative study using the integrated model of health literacy - Juliana Namutundu; Juliet Kiguli; Edith Nakku-Joloba; Fredrick Makumbi; Fred C. Semitala; Rhoda K. Wanyenze; Miriam Laker-Oketta; Damalie Nakanjako; Miriam Nakalembe (BMC, 2024)
Abstract Background Several rural public health facilities in East Central Uganda have sub-optimal, below 50%, levels of uptake of cervical cancer screening services among women with HIV. This is attributed to low cervical cancer screening literacy: limited ability to access, understand, appraise, and apply cervical cancer screening information. This research identified multi-level (health facility, community, interpersonal and individual) barriers, and facilitators of accessing, understanding, and applying cervical cancer screening information among rural women with HIV attending rural public health facilities in East Central Uganda to inform interventions. Methods We conducted ten Focus Group Discussions with rural women aged 25-49 years with HIV attending four selected rural public health facilities: thirty women who had ever screened for cervical cancer and thirty women who had never screened for cervical cancer across different age categories. Data was collected using a guide based on the Integrated model of health literacy. Thematic analysis was used for analysis. Competences (accessing, understanding and applying cervical cancer screening information) and categories of factors (health system, community, interpersonal and individual factors) of the integrated model of health literacy were deductively derived whereas barriers and facilitators were deductively derived from women's statements. Results Lack of communication materials and inability to access information were health facility and individual barriers of accessing cervical cancer screening information respectively. Facilitators of accessing information were access to information at health facility, community, and interpersonal levels and women's ability to access information. Barriers and facilitators of understanding cervical cancer information were related to communication materials, provision of health education and women's concentration during health education. Barriers and facilitators of applying cervical cancer screening information were related to communication and provision of cervical cancer screening services at health facility level, and interpersonal level from peers, partners and other family members as well as women's ability to: understand information and access to cervical cancer screening services at individual level. Conclusions This study emphasizes the influence of multi-level factors on cervical cancer screening literacy among rural women with HIV attending rural public health facilities in East Central Uganda. Improving uptake of cervical cancer screening services among these women requires multi-level interventions.